Strategic Vigilance and its Role in Achieving Marketing Creativity: An Analytical Study of the Opinions of Managers in a Number of Tourism Companies and Offices in the Kurdistan Region-Iraq - كاكە صديق, پشدەر; فريدون عبدالله , ده رون (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The current research aims to determine the relationship and the effect between strategic vigilance in its dimensions (commercial vigilance, technological vigilance, competitive vigilance, environmental vigilance) and marketing innovation represented by (innovation in service, innovation in pricing, innovation in promotion, innovation in distribution, innovation in individuals (people). ), innovation in operations, creativity in physical evidence) in a number of tourism offices and companies in the Kurdistan region.. After reviewing a set of studies and literature, theoretical concepts and model building and hypotheses were written based on the dimensions of strategic vigilance and marketing innovation, and based on the nature of the research and the goals that it seeks to achieve, it has been relied on the descriptive analytical approach. In order to collect data, a questionnaire was relied on, and (180) questionnaires were distributed to a sample of community members represented by heads of units and administrative departments and supervisors in tourism companies and offices in the Kurdistan Region of Iraq. After sorting and checking the received forms, the number of questionnaires valid for analysis reached (139) after excluding (7) questionnaires that were not valid for analysis. Several statistical methods were used, including arbitrators and Cronbach's alpha to verify validity and reliability, simple correlation and structural equation modeling using (SPSS-26) and (AMOS-26). The results showed a positive correlation and impact between the research variables and its dimensions. Based on the results of the research, a number of recommendations were made related to the need for managers, heads of units and leaders in tourism companies in the Kurdistan Region to focus on strategic vigilance practices in order to achieve marketing creativity for the companies investigated.